2022
DOI: 10.1088/1755-1315/1038/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Sustainable Biogas Production from Macroalgae in Indonesia

Abstract: Indonesia is the second world’s major macroalgae producer after China, contributing to 28% of the global macroalgae production. Indonesia increased its macroalgae farming output from less than 4 million tons in 2010 to over 9.9 million tons in 2019. It is expected to continue rising to 13 million tons by 2024. The contribution of macroalgal products is quite significant, 60.7% of the total national aquaculture production. To achieve sustainable energy development goals in many developing countries, including I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Even regionally in ASEAN, Indonesia and Malaysia appear to be actively discussing issues related to "sustainable development" in various aspects such as "sustainable biogas production" (Farobie et al, 2022); "Application of the SDG principles interior architecture" (Affandi et al, 2022); "Sustainable interior economy planning" (Marsahala et al, 2023); "ecolabel and certification (Rais & Suzianti, 2021) and so on. As we move towards the achievement of the SDGs by 2030, themes related to "sustainability" "climate change" and "environmental protection" are increasingly popular for study.…”
Section: Discussionmentioning
confidence: 99%
“…Even regionally in ASEAN, Indonesia and Malaysia appear to be actively discussing issues related to "sustainable development" in various aspects such as "sustainable biogas production" (Farobie et al, 2022); "Application of the SDG principles interior architecture" (Affandi et al, 2022); "Sustainable interior economy planning" (Marsahala et al, 2023); "ecolabel and certification (Rais & Suzianti, 2021) and so on. As we move towards the achievement of the SDGs by 2030, themes related to "sustainability" "climate change" and "environmental protection" are increasingly popular for study.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a UV-Vis Spectrophotometer (Type U-2900, HITACHI, Japan) was used to analyze the products of the bio-pigments at wavelengths of 750, 651, 618, 614, 565, and 498.5 nm. The phycoerythrin content was calculated following a previous study [11], as shown in Equation (1).…”
Section: Calculation Of Bio-pigmentsmentioning
confidence: 99%
“…Indonesia is a maritime country with a broader water area than land. Indonesia also has abundant marine resources consisting of animal and vegetable resources, such as coral reefs and marine macroalgae, commonly called seaweed [1]. Marine macroalgae are large algae, ranging from several centimeters (cm) to many meters.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of Undaria pinnatifida and Hizkia fusiformis has also been shown to improve overall body weight Available at www.veterinaryworld.org/Vol.17/February-2024/27.pdf gain and egg-laying performance in laying hens [16]. Considering that Indonesia is one of the world's major macroalgae producers with more than 500 macroalga species [17], the prospect of utilizing macroalgae as animal feed is promising. A locally available and easily accessible natural ingredient may be a good alternative to animal feed.…”
Section: Introductionmentioning
confidence: 99%